1994
DOI: 10.1002/polb.1994.090321012
|View full text |Cite
|
Sign up to set email alerts
|

P‐V‐T properties of alternating poly(ethylene‐propylene) liquids

Abstract: The pressure‐volume‐temperature (P‐V‐T) properties of monodisperse alternating poly(ethylene‐propylene) (hydrogenated polyisoprene) melts of varying molecular weights are measured at 0.1 MPa < P < 200.1 MPa, and 290 K < T < 510 K in a dilatometer‐type apparatus. The Flory‐Orwoll‐Vrij (FOV), Modified Cell Model (MCM), Sanchez‐Lacombe (SL), and the Statistical Associating Fluid Theory (SAFT) equations of state are found to correlate the experimental data with excellent accuracy, except either at low pressures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…The SAFT EOS parameters characterize the effective chain segment of copolymer, and especially, are independent of molecular weight [2]. The modified cell model (MCM) and the Simha-Somcynsky (SS) EOS are the most accurate relations for representation of polymer melts PVT as considered by Rodgers [6].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The SAFT EOS parameters characterize the effective chain segment of copolymer, and especially, are independent of molecular weight [2]. The modified cell model (MCM) and the Simha-Somcynsky (SS) EOS are the most accurate relations for representation of polymer melts PVT as considered by Rodgers [6].…”
Section: Theorymentioning
confidence: 99%
“…Zoller et al [1] measured PVT of poly(vinyl acetate)/polyethylene copolymer and discussed in terms of the sequential structure of the copolymer chain. PVT properties of monodisperse alternating poly(ethylene-propylene) (hydrogenated polyisoprene) melt of varying molecular weights were measured by Chen et al [2]. They reported that parameters of the statistical associating fluid theory (SAFT) equation of state were independent of molecular weight.…”
Section: Introductionmentioning
confidence: 98%
“…During the line fitting, phases were fixed to 31.0 and 34.4 ppm, respectively, relative to the orthorhombic crystalline peak that was set to 33.0 ppm. [3][4][5][6] The program fitted the chemical shift of the interfacial PE. Estimated error in the measurements of mass fractions derived from measurements in the present work is of the order of Ϯ 0.02.…”
Section: Line-fitting Proceduresmentioning
confidence: 99%
“…The detection of monoclinic phases of polyethylene with similar CP MAS 13 C NMR spectra is reported. [3][4][5][6][7]13 The quantification of the monoclinic fraction through line-fitting procedures depend on setting a fixed chemical shift of this monoclinic fraction due to this lack of resolution. In the present work the size of the monoclinic fraction will be somewhat sensitive to the chemical shift chosen.…”
Section: Analyses Of the Hdpe Extrusion Coating Layermentioning
confidence: 99%
“…In this way, a wide range of polyHIPE-supported functional groups was obtained, from alkyl or aryl amines to acids through halogens, alcohols, aldehydes, esters, and many other derivatives obtained by solid-phase chemical modification. 2 Cross-polarity/magic-angle spinning (CP/MAS) 13 C NMR is a good tool to evaluate a polymer's structure because it has many intrinsic advantages. Cross-polarization enables a spectrum to be acquired very quickly, with a better signal-to-noise ratio.…”
Section: Introductionmentioning
confidence: 99%